Friday

April 18, 2014

April 18, 2014

Posted by **alexis** on Tuesday, September 1, 2009 at 5:46pm.

- algebra -
**Martha**, Tuesday, September 1, 2009 at 9:29pm-1 1/3 f = -5/9

change -1 1/3 to an improper fraction, which will be -4/3.

So -4/3 f = - 5/9

Multiply both sides of the equation by -3/4. Doing this makes the coefficient of f become 1.

Thus (-4/3)(-3/4) f = (-5/9)(-3/4)

1f = - 5/12

**Related Questions**

Algebra - Solve for x: h=(k/4)(x-3L) Solve for B: v-6Bxk=7B Solve for S: z+(1/7)...

math (college algebra) - Ok I have two questions I have NO CLUE how to complete ...

algebra - solve the formula for the given letter. Assume all variables represent...

algebra - Plug in (-1) for x. It will look like this: f(-1) = 4 *(-1) - 3 four ...

Algebra - I'm trying to solve the problem: 6y-bracket 3y-(y+7)bracket. I got an ...

ALGEBRA 3 - if f{x}= negative x square - 7x - 22, what is f{negative 5}? a....

Algebra - 91. Find the domain of: y=-3x+1 a. all negative numbers b. x>0 c. ...

math--pre alg - not sure i did right 3(f+2)+9=13+5f 3f+6+9 = 13+5f +9 3F+15 = 12...

Pre Algebra - how do i do to get the answer for negative 12 + possitive 4+...

algebra 3 - which number is a the solution of the equation [5x-2] = 8? a.}6/5 b...